Hemostatic efficacy of TachoSil in liver resection compared with argon beam coagulator treatment: an open, randomized, prospective, multicenter, parallel-group trial - Fischer, Lars; Seiler, Christoph; Broelsch, Christoph E.; de Hemptinne, Bernard; Klempnauer, Jürgen; Mischinger, Hans-Jörg; Gassel, Heinz-Jochen; Rokkjaer, Mogens; Schauer, Rolf; Larsen, Peter N.; Tetens, Vilhelm; Büchler, Markus W. (Surgery, 2011)
Background: The aim of this trial was to confirm previous results demonstrating the efficacy and safety of a fixed combination tissue sealant versus argon beam coagulation (ABC) treatment in liver resection. Methods: This trial was designed as an international, multicenter, randomized, controlled surgical trial with 2 parallel groups. Patients were eligible for intra-operative randomization after elective resection of ≥1 liver segment and primary hemostasis. The primary end point was the time to hemostasis after starting the randomized intervention to obtain secondary hemostasis. Secondary end points were drainage duration, volume, and content. Adverse events were collected to evaluate the safety of treatments. The trial was registered internationally (Eudract number 2008-006407-23). Results: Among 119 patients (60 TachoSil and 59 ABC) randomized in 10 tertiary care centers in Europe, the mean time to hemostasis was less when TachoSil was used (3.6 minutes) compared with ABC (5.0 minutes; P = .0018). The estimated ratio of mean time to hemostasis for TachoSil/ABC was 0.61 (95% confidence interval, 0.47-0.80; P = .0003). Postoperative drainage volume, drainage fluid, and drainage duration did not differ between the 2 groups. Mortality (2 vs 4 patients) and adverse reactions (24 vs 28 patients) for TachoSil versus ABC did not differ. Conclusion: This trial confirmed that TachoSil achieved significantly faster hemostasis after liver resection compared with ABC. Postoperative morbidity and mortality remained unchanged between both groups.
Online verfügbar: 10. April 2010
Gesehen am 07.12.2022